Erros de escrita em inglês por brasileiros: identificação, classificação e variação entre níveis - Dantas, Wendel Mendes (2012)
The aim of this study was to identify and classify errors found in Brazilian English learners s written tasks. The questions which guide this research are: Which are the most common errors in COBRA-7_recorte? ; What is the error variation among course levels for learners found in COBRA-7_recorte? and Which course level shows the highest error diversity in COBRA-7_recorte?". The main theoretical underpinning for the research is provided by Corpus Linguistics, an area devoted to the collection and criterious analysis of data collected from texts in electronic formar, and, specifically, by research on learner corpora. the corpora used in this research were the Corpus of Contemporary American English (COCA) (consultation corpus) and a sample of COBRA-7 (COBRA-7_recorte), the study corpus, compiled from the writings of adult learners enrolled in a network of schools which teach English as a foreign language in the state of São Paulo, and which have been produced between 2009 and 2010. The data have been collected from the institution's online server in 2011. Results have shown that the most common errors found in the analysis corpus are: wrong lexical choice, tense and aspect use, use of determiners, and wrong use of questions, negatives or auxiliaries. They have also revealed that pre-intermediate course level has the highest quantity and diversity of errors, probably because it is a level at which learners are exposed to diverse verbal tenses. Finally, this study has also shown that although wrong lexical choice, particularly the replacement of prepositions or particiles by words from the same or other grammatical categories, seem to be a problem for learners, this difficulty tends to decrease along the course, unlike errors of verbal tense and aspect use, which tend to increase